Maternal exposure to di-n-butyl phthalate (DBP) induces renal fibrosis in adult rat offspring - Zhu, Yi-Ping (Oncotarget, 2017)
This study was to determine the impact of maternal exposure to di-n-butyl phthalate (DBP) on renal development and fibrosis in adult offspring. Pregnant rats received DBP at a dose of 850 mg/kg BW/day by oral perfusion during gestational days 14–18. In DBP exposed newborn offspring, gross observation and histopathological examination revealed the dysplasia of kidney. The expression of genes related to renal development was also changed. In DBP exposed adult offspring, histopathological examination and Masson's trichrome staining revealed the pathological changes of renal fibrosis. Furthermore, higher expression levels of transforming growth factor- β (TGF-β) and alpha-smooth muscle actin (α-SMA) were also detected. In vitro studies reveal that DBP promoted the activation of NRK49F cells and G2/M arrest in NRK52E cells at a sublethal dose. The effect of DBP on these cell lines was linked to the generation of oxidative stress. In addition, DBP induced oxidative stress in both renal fibroblasts and tubular epithelial cells, whereas vitamin C ameliorated the changes caused by DBP. In conclusion, our results showed that prenatal exposure to DBP may generate oxidative stress in both renal fibroblasts and tubular epithelial cells, leading to kidney dysplasia and renal fibrosis.